(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
Community-Based Tourism (CBT) has become an effective tool for rural development in Indonesia, enabling local communities to leverage their assets for economic, social, and environmental sustainability. This study examines Pentingsari Tourism Village, established in 2008 in Yogyakarta, through the combined lenses of the Asset-Based Community Development (ABCD) framework and market analysis. Using a qualitative case study approach, data were collected through focus group discussions, presentation from tourism leader, field observations, and secondary sources. The findings show that Pentingsari has successfully mobilized its assets, 137 households, cultural traditions, agricultural landscapes, and strong social cohesion, into a vibrant tourism model. In 2023, Penting Sari generated IDR 3.3 billion in revenue, with 92% distributed to the community and 8% to the village fund, illustrating equitable economic benefits. Market analysis highlights family-based recreation, educational tourism, and eco-cultural immersion as key visitor segments. Sustainability practices include gender equality in governance, involvement of marginalized groups (elderly, disabled, and minorities), and environmental stewardship through waste segregation, recycling, and biogas production. International recognition, such as the UNWTO Award (2011) and the ASEAN Tourism Award for CBT (2023), confirms Pentingsari’s status as a leading model of CBT. The study concludes that integrating ABCD and market analysis strengthens sustainable tourism by aligning community assets with market opportunities, offering both theoretical insights and practical strategies for rural tourism development.